Challenges and Opportunities for Seafarer Training in the Context of a Modernizing Maritime Industry: Research Overview - Mickevičiūtė, Indrė (Vilnius University Open Series, 2020)
The aim of this article is to analyze and systematize the research examining the process of training seafarers, in a time when the rapidly modernizing maritime industry presupposes the need for educational transformation change. The analysis of the research reveals that some research on this topic focuses more on the development of autonomous vessels, presents the idea of the Shore Control Center, where operators will manage autonomous vessels. Other researchers emphasize the importance of social skills and emotional intelligence in the process of training seafarers. The training of seafarers is a long-term process in which the harmonization of educational paradigms, based on values, comprehensively covering the formation of personality traits, general competencies, professional knowledge and skills, would create preconditions for the training of highly qualified seafarers.